The Web Service Challenge - A review on Semantic Web Service Composition - Bleul, Steffen; Weise, Thomas; Geihs, Kurt (Electronic Communications of the EASST, 2009)
Every year, contesters submit contributions to the Web Service Challenge (WSC) in order to determine which service composition system is the most efficient one. In this challenge, semantic composition tasks must be solved and the results delivered by the composers are checked for correctness. The time needed for the composition process is another important competition criterion.After we had participated with great success in the 2006 and 2007 WSC, we were asked to manage the Web Service Challenge 2008. In this paper, we present the challenge task, the challenge rules, the document format used, and the results of this competition. We provide a summary over the past challenges and give first previews on the future developments planned for the Web Service Challenges to come.